2005
DOI: 10.1021/jp045922t
|View full text |Cite
|
Sign up to set email alerts
|

Entropy−Enthalpy Compensations in Solutions of Dual Character Molecules with Polymeric Chromatographic Liquid Phases

Abstract: Careful gas chromatographic studies provide thermodynamic data for insights into solution processes in nonvolatile solvents. Using 24 solutes and five stationary phases, several entropy-enthalpy compensation effects in the thermodynamics of solution were identified. Despite solute structure differences, when excess enthalpy and entropy of solutions were examined, entropy-enthalpy compensation effects were found in solvents dominated by single types of interaction: squalane and, to some extent, methoxy poly(eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In this study, it is proposed to avoid the difficulty associated with the solid reference state by studying the difference of thermodynamic properties of the solute between two solvents; that is, the transfer thermodynamic functions between the two solvents. In a recent study Huang et al [16] proposed that the effects of liquid-state interaction of a liquid solute could be removed by comparing solution properties of the solute between two solvents. The solid-state interaction of a solute will also be cancelled in the calculation of transfer properties between two solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is proposed to avoid the difficulty associated with the solid reference state by studying the difference of thermodynamic properties of the solute between two solvents; that is, the transfer thermodynamic functions between the two solvents. In a recent study Huang et al [16] proposed that the effects of liquid-state interaction of a liquid solute could be removed by comparing solution properties of the solute between two solvents. The solid-state interaction of a solute will also be cancelled in the calculation of transfer properties between two solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In examining the solubility of a solute in solvents the combination of Hildebrand solubility parameter model [14,15] and Flory-Huggins theory [16] is commonly used. In this method the activity coefficient is considered to be the product of two components: the athermal or Flory-Huggins part, γ F-H , and thermal part, γ T :…”
Section: Introductionmentioning
confidence: 99%
“…This quantity is proportional to the transfer free energy for solutes to move from one polymer to another polymer. It was pointed out by Huang et al 14 that in calculating transfer properties of a solute between two solvents the solute liquid state interaction of all probes can be eliminated. Therefore, the large contribution of hydrogen bonding interaction in the solute liquid state in alcohols is removed when transfer properties are used.…”
Section: Prediction Of Miscibility Of Pcl-pech Blendmentioning
confidence: 99%
“…[3][4][5][6][7][8] From sorption data of low molecular weight solutes in polymers at several temperatures one can obtain the enthalpy and entropy of the solution process. In a recent study Huang et al 9 showed that linear entropy-enthalpy relationship was observed in IGC study of solutes in a nonpolar hydrocarbon solvent and a polar polyethylene oxide solvent. For some moderately polar solvents the correlation was less noticeable.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the variation in solution properties among solutes reflects the difference in interaction within pure solute liquids. 9 Thus, one might see a good correlation between heat of vaporization and enthalpy of solution for solutes in nonpolar solvents. This is explored in the present study.…”
Section: Introductionmentioning
confidence: 99%